A10.25 Synovial Tissue Transcriptome and Synovial Fluid Proteome have Stronger Discriminatory Power than Serum in Dissecting Inflammation in RA. (25th February 2013) - Smiljanovic, Biljana; Stuhlmueller, Bruno; Pade, Silvia; Backhaus, Marina; Burmester, Gerd-R; Radbruch, Andreas; Grützkau, Andreas; Häupl, Thomas
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is a chronic disease associated with polyarticular inflammation, cartilage and/or bone destruction. Current diagnosis of RA is based on clinical criteria and measurement of non-specific makers of inflammation in the blood. A main challenge in diagnosis of RA is to establish objective criteria able to provide a more detailed insight into joint pathobiology. In search for convenient biomarkers, gene-expression profiles from synovial tissues of RA and osteoarthritis (OA) patients were generated. These profiles were used for selection of candidate biomarkers that were measured at the protein level both in synovial fluid and matched serum samples from RA and OA patients. Materials and Methods: Gene-expression profiles from synovial tissues of RA and OA patients were generated by Affymtetrix HG-U133A arrays. The BioRetis database was used for array analyses and selection of RA candidate genes. ELISA and multiplex immunoassays were used for validation of the candidate markers at the protein level. Results: Transcriptome analyses of synovial tissues from RA and OA patients revealed more than 1000 differentially expressed genes. Genes involved in chemotaxis, inflammation, cell adhesion and activation were strongly up-regulated in patients with RA. In total, 20 genes out 1000 were used for validation at the protein level, including 1) cytokines: IL8, MIF, MIG, CXCL13, CCL18; 2) the shedded form of membrane molecules: sCD14, sCD163, sCD44, uPAR, sICAM1, sVCAM1, P- Selectin, E-Selectin; and 3) markers related to bone destruction and bone formation: NTxI and PINP. These molecules were measured both in SF and matched serum samples from RA and OA patients. Protein levels of all these markers were elevated in SF of RA patients, showing an obvious inflammatory profile that clearly discriminated RA from OA. Serum levels of these markers were elevated in RA patients, compared to OA and/or healthy donors (ND) as well. Among all serum markers CXCL13, sCD14, CCL18, PINP and NTxI disclosed the highest level of specificity and sensitivity. Nevertheless, the potential of serum markers in general to discriminate RA from OA and/or ND was far weaker compared to those in SF. Conclusions: Disease-specific profiles were evident in the joint where both synovial tissue transcripts and related SF proteins revealed a clear differences between RA and OA. Despite blood is a favourable diagnostic material, the results from this study indicated that the capacity of blood to dilute and neutralise inflammation is robust enough to limit discrimination between RA and OA.